Fluid-particle heat transfer in fixed and fluidized beds - Gupta S.N.; Chaube R.B.; Upadhyay S.N. (My University, 2025)
Fluid-particle heat transfer in fixed and fluidized beds is re-examined. The heat transfer factor depends not only on the particle Reynolds number but also on the void fraction of the bed. The available experimental data has been correlated to yield a non-linear relationship between ε{lunate}Jh and the particle Reynolds number. The resulting expression is: {A figure is presented}. © 1974.